2020
DOI: 10.1111/cpf.12626
|View full text |Cite
|
Sign up to set email alerts
|

Specific slow tests are not mandatory in patients with extremely short standard (3.2 km/hr 10% slope) test durations during exercise oximetry

Abstract: Aim To compare the transcutaneous oxygen pressure results observed in patients with severe walking limitation during standard procedures (3.2 km/hr, 10% slope) versus during a test performed at a low speed (2 km/hr, 10% slope). Methods In 31 patients, the decrease from rest of oxygen pressure (DROP) index was measured on both buttocks, both thighs and both calves during two consecutive tests on treadmill. The maximal walking time (MWT) and the minimal DROP values (DROPmin) observed during the 2 tests were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…DROPmin has been validated as a sensitive and specific indicator for exercise-induced ischemia for both proximal and distal arterial claudication. A previous study showed that the treadmill procedure had little influence on exercise-oximetry results in the patients that were candidates for a slow treadmill procedure [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…DROPmin has been validated as a sensitive and specific indicator for exercise-induced ischemia for both proximal and distal arterial claudication. A previous study showed that the treadmill procedure had little influence on exercise-oximetry results in the patients that were candidates for a slow treadmill procedure [ 23 ].…”
Section: Methodsmentioning
confidence: 99%